School work guides: an experience for recognizing, valuing and appropriating environmental wealth - Rojas Suarez, Yancy Judith; Hernández Barbosa, Rubinsten (Revista Universitaria del Caribe, 2021)
The planetary pandemic situation experienced in 2020 generated changes in the way some educational activities were regularly carried out; technologies were used for the development of classes; however, these resources were not available in all institutions. Due to this situation, this text describes the experience of designing school work guides for eighth grade students at Antonio Nariño Technical Educational Institution, Boyacá, Colombia, as a resource for recognizing and valuing environmental wealth. The guides are designed and validated with experts considering objectives, structure, resources and diversity of activities, among other aspects. It was a space to rethink the purposes of the school, the ways of learning and the importance of approaching students, from the natural sciences classes, to recognize and value the environmental wealth of the municipality.